PERBANDINGAN PENGATURAN KEDUDUKAN WARIS WARGANEGARA ASING DI INDONESIA DENGAN TURKI - Agnes Odelia; Wahyuni Retnowulandari; Bahasa Indonesia (Reformasi Hukum Trisakti, 2023)
In developing legal and policy reforms in Indonesia through comparing existing laws in Indonesia with existing laws in other countries. This research focuses on comparing the arrangements for the inheritance position of foreign in Indonesia and in Turkey, main problem are what are the similarities and differences in inheritance arrangements in Indonesia and in Turkey and what is the position of the heirs of foreign citizens in cases in Indonesia and in Turkey based on Civil Code and TMK and MÖHUK. This research method is normative in the form of legal comparisons to obtain similarities and differences in regulations, while the nature of the research is descriptive and conclusions are drawn deductively. The results of the research and discussion are that there are differences and similarities regarding inheritance law in Indonesia which is pluralistic and inheritance law in Turkey which is unification. The conclusion is that both of them do not see a difference regarding nationality between the heir and his heirs and in resolving the cases in Indonesia and Turkey, both give the same inheritance rights to the heirs of foreign with the same shares as the heirs of the heirs' national citizens